Time-spatial analysis of T cell receptor repertoire in esophageal squamous cell carcinoma patients treated with combined radiotherapy and PD-1 blockade. (31st December 2022) - Yan, Cihui; Ma, Xiaoxue; Guo, Zhoubo; Wei, Xiaoying; Han, Dong; Zhang, Tian; Chen, Xi; Cao, Fuliang; Dong, Jie; Zhao, Gang; Gao, Xuan; Wang, Tao; et al.
ABSTRACT: T cell receptor (TCR) repertoire as a biomarker for predicting immunotherapy efficiency has been widely studied. However, its dynamics during radiotherapy combined with PD-1 blockade is little known. Using paired tumor and blood samples from the phase Ib clinical study (NCT03222440), we investigate the time-spatial TCR repertoire in esophageal squamous cell carcinoma (ESCC) patients treated with first-line definitive radiotherapy concurrently with anti-PD-1 antibody camrelizumab, and also evaluate the association between TCR repertoire and clinical outcomes. TCR sequencing was performed on tumor biopsies (n = 34, 15 pairs) and peripheral CD8 + T cells (n = 36, 18 pairs) collected at baseline and during treatment (after 40 Gy radiation and 2 rounds of camrelizumab). Whole exome sequencing was applied to estimate genomic mutations and tumor mutation burden. We show that the intratumoral TCR repertoire at baseline was correlated with tumor microenvironment and presented heterogeneity inter-individually. T-cell clones inflowed mutually between tumors and peripheral blood under combination treatment, resulting in an elevation of intratumoral TCR diversity. The peripheral CD8 + TCR diversity at baseline, increased tumor-peripheral Morisita-Horn overlap during treatment, and expansion of persistent intratumoral T-cell clones during treatment predicted improved survival. While it is unclear whether radiation contributed to the TCR changes versus PD-1 therapy alone, our results firstly reveal radiotherapy combined with PD-1 blockade greatly promoted time-spatial alteration of TCR repertoire between tumor and peripheral blood, which demonstrate the peripheral CD8 + TCR diversity at baseline and dynamic alteration of intratumoral TCRs acted as potential effective biomarkers of radiotherapy combined with immunotherapy in ESCC.